Computed-Tomography Estimates of Interaural Mismatch in Insertion Depth and Scalar Location in Bilateral Cochlear-Implant Users. Issue 6 (July 2022) - Goupell, Matthew J.; Noble, Jack H.; Phatak, Sandeep A.; Kolberg, Elizabeth; Cleary, Miranda; Stakhovskaya, Olga A.; Jensen, Kenneth K.; Hoa, Michael; Kim, Hung Jeffrey; Bernstein, Joshua G. W.
Abstract : Hypothesis: Bilateral cochlear-implant (BI-CI) users will have a range of interaural insertion-depth mismatch because of different array placement or characteristics. Mismatch will be larger for electrodes located near the apex or outside scala tympani, or for arrays that are a mix of precurved and straight types. Background: Brainstem superior olivary-complex neurons are exquisitely sensitive to interaural-difference cues for sound localization. Because these neurons rely on interaurally place-of-stimulation-matched inputs, interaural insertion-depth or scalar-location differences for BI-CI users could cause interaural place-of-stimulation mismatch that impairs binaural abilities. Methods: Insertion depths and scalar locations were calculated from temporal-bone computed-tomography scans for 107 BI-CI users (27 Advanced Bionics, 62 Cochlear, 18 MED-EL). Results: Median interaural insertion-depth mismatch was 23.4 degrees or 1.3 mm. Mismatch in the estimated clinically relevant range expected to impair binaural processing (>75 degrees or 3 mm) occurred for 13 to 19% of electrode pairs overall, and for at least three electrode pairs for 23 to 37% of subjects. There was a significant three-way interaction between insertion depth, scalar location, and array type. Interaural insertion-depth mismatch was largest for apical electrodes, for electrode pairs in two different scala, and for arrays that were both-precurved. Conclusion: Average BI-CI interaural insertion-depth mismatch was small; however, large interaural insertion-depth mismatch—with the potential to degrade spatial hearing—occurred frequently enough to warrant attention. For new BICI users, improved surgical techniques to avoid interaural insertion-depth and scalar mismatch are recommended. For existing BI-CI users with interaural insertion-depth mismatch, interaural alignment of clinical frequency tables might reduce negative spatial-hearing consequences.